(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
Simon Bolivar and Rafael Urdaneta were the most outstanding heroes of Venezuela Independence War, which took place between 1880 and 1888. Bolivar’s and Urdaneta’s one hundredth birthday anniversary was used to strengthen the notion of Venezuelan Nation. This celebration was held within a political crisis during which the elite and the people of Maracaibo struggled to consolidate a feeling of nation by a sense of belonging both locally and regionally. This struggle was the answer to Guzman Blanco’s government against Zulia’s autonomy. The organization of the centennial made it possible to create an image of progression of the region and it also gave it the necessary merits to make a living as an independent entity.